2021
DOI: 10.1016/j.ymthe.2020.09.024
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Long Non-Coding RNA LINC00618 Accelerates Ferroptosis in a Manner Dependent upon Apoptosis

Abstract: Ferroptosis is primarily caused by intracellular iron catalytic activity and lipid peroxidation. The potential interplay between ferroptosis and apoptosis remains poorly understood. Here, we show that the expression of a nuclear long non-coding RNA (lncRNA), LINC00618, is reduced in human leukemia and strongly increased by vincristine (VCR) treatment. Furthermore, LINC00618 promotes apoptosis by increasing the levels of BCL2-Associated X (BAX) and cleavage of caspase-3. LINC00618 also accelerates ferroptosis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(134 citation statements)
references
References 57 publications
4
123
0
Order By: Relevance
“…The mRNA promotes ferroptosis by increasing the levels of lipid ROS and iron, while decreasing the expression of SLC7A11 . It further induces vincristine-induced ferroptosis and apoptosis of 12 . In a related study, Lu et al 13 found that in acute ischemic stroke, lncRNA PVT1 regulated ferroptosis via miR-214, which modulates the expression of TFR1 and TP53 .…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA promotes ferroptosis by increasing the levels of lipid ROS and iron, while decreasing the expression of SLC7A11 . It further induces vincristine-induced ferroptosis and apoptosis of 12 . In a related study, Lu et al 13 found that in acute ischemic stroke, lncRNA PVT1 regulated ferroptosis via miR-214, which modulates the expression of TFR1 and TP53 .…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis, a unique cell death, characterized by the stimulation of reactive oxygen species (ROS) result in the mitochondria dysfunction induced by iron catalytic activity and lipid peroxidation [41]. Growing studies has shown that ferroptosis was also a critical form of cardiomyocytes death [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…GABBB1 and its antisense chain lncRNAGAPB1-AS1 can interact in erastin-induced ferroptosis; GAPBB1 and GAPBB1-AS1 can be used as therapeutic targets for liver cancer 46 . Lymphoid-specific helicase (LSH) can increase the transcription of SLC7A11 after the recruitment to the promoter regions of SLC7A11, and LINC00618 can reduce the expression of LSH, thus inhibiting ferroptosis 47 (Fig. 7 ).…”
Section: Lncrna Regulates Ferroptosismentioning
confidence: 99%